Iatrogenic secondary subfertility with anovulation: A case study (Journal of Chittagong Medical College Teachers' Association, 2009)
doi: 10.3329/jcmcta.v19i1.3852Journal of Chittagong Medical College Teachers' Association 2008: 19(1):43-45